Struktur Modal, Penyaluran Kredit, dan Profitabilitas Perbankan Konvensional - Lestari, Dinda Putri; Sihono, Agus (Juara: Jurnal Riset Akuntansi, 2025)
This research was conducted to find out whether capital structure, operational costs and credit distribution can influence profitability. The ROA proxy is used to measure profitability, the DER proxy is used to measure capital structure, the LDR proxy is used to measure credit distribution, and operational costs are measured by comparing operational costs with income. Banking sector entities on the Indonesian Stock Exchange (BEI) from 2020 to 2022 as population. Purposive sampling technique to determine the sample, the criteria used are entities that have profits during the research period. So that the sample that can be used is 87 financial reports from 29 entities. This research uses a causalization design. Using multiple regression analysis techniques, this research shows that capital structure does not have a significant impact on profitability, operational costs do not have a significant impact on profitability, and credit distribution has a significant impact on profitability in a positive direction. The implications of this research provide input to shareholders on the importance of managing company assets to obtain good profitability.